(3TQM TPhQ GdPgHs - (3Ydj Hf ehSi GdCfOdSj GdeYQha HGHf CQaY QCSs; (3YHO Gdedc Hf gTGe Hf CjhH GdMejQj GdeYGaQj, CHh eMeO, LeGd GdOjf,J (B213 (3g` s
(3ChdgG (B:s
(3bGd GdaGVd GdYdGeI CHh GdbGSe GdCfUGQi SCdJ SjOi hehdGi Yf eYfi bhdg ai jhGfg GdPi de jSHbg Edi eKdg CMO GdJKdjK s
(3BNQgG (B:s
(3ade CJhba ai Pdc cJhba LYaQ dLGHQ Hd HGOQJ aCLHJ Edi Pdc hddg GdMeO hGdefI Je HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO GdYfhGf GdCUdi (B2 / 1029s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B166 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B192s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs